Seven new species and new distributional records of Trizogeniates Ohaus, 1917 (Coleoptera: Scarabaeidae: Rutelinae) with a key and illustrated checklist of Brazilian species - Ferreira, André Da Silva; Bravo, Freddy; Grossi, Paschoal C.; Seidel, Matthias (Zootaxa, 2019)
Seven new species of Trizogeniates Ohaus, 1917 (Coleoptera: Scarabaeidae: Rutelinae: Geniatini) from Brazil are described: Trizogeniates beckeri new species, T. curvatus new species, T. eliskae new species, T. hallensorum new species, T. spatulatus new species, T. vazdemelloi new species, and T. zuzanae new species. The male of T. eris Villatoro, 2002 is described for the first time. The diagnostic features of the seven new species and the male of T. eris are presented and compared with their congeners. Illustrations of specimens, mouthparts, and male genitalia of the new species and T. eris are also provided. Additionally, an identification key and an illustrated catalogue with the geographic distribution of the Brazilian species of Trizogeniates are presented. New Brazilian state records for 12 species are depicted: T. cribricollis (Lucas, 1859) from Pará, Mato Grosso do Sul, and Paraná; T. dispar (Burmeister, 1844) from Espírito Santo; T. eris from Rio de Janeiro; T. goyanus Ohaus, 1917 from Mato Grosso do Sul; T. laevis (Camerano, 1878) and T. montanus Ohaus, 1917 from Espírito Santo and Paraná; T. temporalis Ohaus, 1917 from Goiás; T. terricolus Ohaus, 1917 and T. vittatus (Lucas, 1859) from Paraná; and T. traubi Martínez, 1965 from Pará, Minas Gerais, and São Paulo. Finally, distributional maps for the Brazilian species are included.